NILAI-NILAI PENDIDIKAN PEREMPUAN DALAM TAFSIR AL-MARAGHI (Kajian Q.S An-Nisa’ Ayat 34-36, Q.S Al-Ahzab Ayat 59 dan Q.S An-Nur Ayat 31) - Muriyah Pasaribu, Achyar Zein, Syamsu Nahar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstact: This study aims to analyze: 1) How should Musthofa al-Maraghi interpret verses about women?2) What are the values of women’s education based on the interpretation of Musthofa al-Maraghi and 3)What is the relevance of women’s educational values contained in the Qur’an with the current conditionof society. This study uses a qualitative method, using the interpretation method maudu’i, using the primarysource is the Qur’an. Among the interpretation books used are al-Maraghi’s interpretation by Ahmadbin Mustafa al-Maraghi and other exegetes. The results showed that: Musthofa al-Maraghi interpretedverses about women by means of: verse fragments, ijmal meanings, giving meaning to difficult words. Thevalue of women’s education based on Musthofa al-Maraghi’s interpretation is: Aqeedah values, shari’ahvalues, and moral values. The relevance of women’s education values in point two above has a significantcorrelation with the condition of women in society today, especially in terms of teaching and learning suchas not covering genitals, demanding excessive emancipation and following free association. Therefore, thethree values above must be synergized when doing the learning and teaching process.Penelitian ini bertujuan untuk menganalisis: 1)Bagaimana Musthofa al-Maraghi menafsirkan ayat-ayattentang perempuan? 2)Apa nilai-nilai pendidikan perempuan berdasarkan penafsiran Musthofa al-Maraghidan 3)Bagaimana relevansi nilai-nilai pendidikan perempuan yang terdapat dalam Alquran dengankondisi masyarakat saat ini. Penelitian ini menggunakan metode kualitatif, dengan menggunakan pendekatantafsir maudu’i, dengan menggunakan sumber primernya ialah Alquran. Di antara buku tafsir yang digunakanialah tafsir al-Maraghi karya Ahmad bin Mustafa al-Maraghi dan para mufassir lainnya. Hasil penelitianmenunjukkan bahwa: Musthofa al-Maraghi menafsirkan ayat-ayat tentang perempuan dengan cara: potonganpotonganayat, makna ijmal, memberikan makna kata-kata yang sulit. Nilai pendidikan perempuanberdasarkan penafsiran Musthofa al-Maraghi adalah: Nilai aqidah, nilai syari’ah, dan nilai akhlak. Relevansinilai-nilai pendidikan perempuan pada poin dua di atas memiliki korelasi yang signifikan dengan kondisiperempuan di dalam masyarakat saat ini khususnya dalam hal belajar mengajar seperti tidak menutupaurat, menuntut emansipasi yang berlebihan dan mengikuti pergaulan bebas. Oleh karena itu, ketiganilai di atas harus disinergikkan ketika melalukan proses belajar dan mengajar.Kata Kunci: Pendidikan Perempuan dan Tafsir Al-Maraghi